Modelos dinâmicos de magnetização aplicados em compósitos magnetoelétricos - Gualdi, Alexandre José (2014)
In this thesis we study the magnetic properties of the multiferroic composite (1-x)Pb(Mg1/3Nb2/3)-xPbTiO3/CoFe2O4 (PMN-PT/CFO) sintered by hot forging. Magnetization as a function of magnetic field, magnetoelectric effect and magnetostriction effect measurement were carried out at different temperatures. In the magnetization measurements there was a decrease in the value of the saturation magnetization and an increase in the value of the coercive field when compared with a sample of pure ferrite. AC susceptibility as a function of magnetic field measurements showed no change in the value of the in-phase component as a function of the frequency for measurements performed at 5 K. Magnetostriction as a function of the temperature of the samples PMNPT/ CFO and pure CFO measurements showed that the standard model that describes the magnetostrictive behavior was not sufficient to describe the obtained results. To explain the behavior of the magnetostriction was necessary to introduce terms of stress and piezomagnetism in the Gibbs free energy equation. Thus, it was possible to describe the behavior of these materials both at 300 K as at 5 K. In the magnetoelectric effect measurements it was observed that there is a strong dependence on the behavior of the curve with the frequency of the AC magnetic field and temperature. This dependence is associated with the population of the energy levels of the ferromagnetic phase that does not contribute to the magnetostrictive effect. Based on the adiabatic susceptibility model, it was able to describe this dependence in the magnetoelectric effect. Furthermore, we measured the magnetoelectric effect of the composite (1- x)Pb(Mg1/3Nb2/3)-xPbTiO3/NiFe2O4 (PMN-PT/NFO) and compared with the previously results. We didn't observe the same frequency dependence as in the composite sintered with CFO. This result is associated with the spin/orbit energy levels stabilization.